2001
DOI: 10.1093/jn/131.8.2101
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Digestion of Bovine Lactoferrin In Vivo in Adults

Abstract: Lactoferrin (LF), an iron-binding glycoprotein present in milk and other endocrine and exocrine secretions, may exert a number of physiologic effects in the intestines. To study the effects of oral LF supplementation in vivo in the gastrointestinal tract, information about the gastric survival of LF in vivo is important. We tested 12 healthy volunteers (age 21 +/- 0.3 y) on 3 separate d according to a randomized, cross-over design. A test drink containing 4.5 g of bovine LF (20% iron-saturated LF; apoLF) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
119
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(132 citation statements)
references
References 28 publications
5
119
1
Order By: Relevance
“…This implies that at least 76% of the indomethacin was present as free indomethacin after 22 min. In previous studies, we showed that after 7 min almost half of the test drink ingested is emptied from the stomach, while after 22 min most if not all of the test drink is emptied from the stomach into the small intestine (Troost et al, 2001). Hence, in the present study, indomethacin entered the small intestine predominantly unbound to LF.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This implies that at least 76% of the indomethacin was present as free indomethacin after 22 min. In previous studies, we showed that after 7 min almost half of the test drink ingested is emptied from the stomach, while after 22 min most if not all of the test drink is emptied from the stomach into the small intestine (Troost et al, 2001). Hence, in the present study, indomethacin entered the small intestine predominantly unbound to LF.…”
Section: Discussionsupporting
confidence: 63%
“…The observed protective effect of oral LF administration can probably not be explained by LF-indomethacin binding. We previously showed that the major part of orally ingested LF survives gastric passage in vivo in adults, leaving most of the LF intact until it enters the intestine (Troost et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…About 60% of the intact bLF enters the small intestine after oral ingestion. 19 Therefore, we decided to use L-bLF to protect bLF from enzymatic digestion in the stomach. Recently, liposomalization of bLF was shown to improve resistance of bLF to gastric digestion, suggesting that oral administration of L-bLF could be a novel active constituent useful for preventive and therapeutic treatment of inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, bLF is digested by the gastric juice and thus only 60% of the intact bLF enters the small intestine during oral administration. 19 Thus, specific enteric coating or specific delivery systems for bLF are needed for its effective oral administration. Liposomes prepared from naturally occurring biodegradable and nontoxic lipids have been proposed as efficient carriers for local delivery of therapeutic agents.…”
mentioning
confidence: 99%
“…Based on the results of a previous study [32], bovine lactoferrin is easily degraded to digestive enzymes such as pepsin or trypsin, and only 60% of the intact lactoferrin enters the intestine after oral ingestion in human beings. In our study, the degradation and the absorption ratios of bovine lactoferrin that were applied via oral administration in rabbits were not examined.…”
Section: Discussionmentioning
confidence: 99%